High efficiency shear exfoliation for producing high-quality, few-layered MoS2 nanosheets in a green ethanol/water system. Issue 86 (1st September 2016) - Yuan, Hong; Liu, Xiaohong; Ma, Limin; Gong, Peiwei; Yang, Zhigang; Wang, Honggang; Wang, Jinqing; Yang, Shengrong
Abstract : This work presented a feasible strategy to generate molybdenum disulfide (MoS2 ) nanosheets by a direct liquid shear exfoliation technique in a green mixed solvent system of ethanol/water. Abstract : This work presented a feasible strategy to generate molybdenum disulfide (MoS2 ) nanosheets by a direct liquid shear exfoliation technique in a green mixed solvent system of ethanol/water. The volume ratio of ethanol/water and the initial concentration of the bulk MoS2 powders were found to have significant impacts on the final exfoliation yield. The best ratio and initial concentration for optimal shear exfoliation were finally selected as 45 vol% and 10 mg mL −1, respectively. According to the proper shear strength and matching viscosity, systematic analysis on the exfoliation mechanism indicated that shear and collision effects would play the major role when the shearing occurred at a high speed of 10 000 rpm. The higher cumulative yield and better quality (up to 30% after 10 times of shear cycling, comparatively large sizes d ∼ 4 μm) were confirmed by detailed experimental characterizations. Moreover, the photothermal performance was also investigated and the prepared MoS2 nanosheets exhibited great efficiency in transforming near-infrared light into heat. It is expected to be a promising strategy for large-scale production of MoS2 nanosheets with excellent properties in a low-cost and green solvent system.